Peran Spiritualitas-Moralitas Pemimpin Dalam Kitab Hakim-Hakim 19:1-30 - Sihura, Selatieli (JURNAL LUXNOS, 2024)
This article aims to discover the leadership ethics of Judges 19:1-30. This text is filled with edifying teachings about the importance of good ethics-morality of a spiritual leader. A servant of God in his ministry cannot act at will, he always holds the values that are inherent to him, namely the ethics of a servant of God. For a leader, ethics-morality is an important part for him to carry out the duties of his calling. The book of Judges 19:1-30 shows how the ethics of a servant of God did not work properly, marked by the horrific moral decline of the Israelites at that time. This book contains educational teaching. The research method used qualitative research methods including narrative analysis and theological reflection of Judges 19:1-30 with the character of a Levite. The research intends to develop an ethic of leadership that is obedient and in accordance with God's will. The results of this study show that Judges 19:1-30 is a teaching of God's truth actualized through the life of a spiritual leader who lives in righteousness, holiness of self, high ethics and morality.